Towards a Service-Based Internet Third European Conference, ServiceWave 2010, Ghent, Belgium, December 13-15, 2010. Proceedings - Nitto, Elisabetta; Yahyapour, Ramin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of the Third European Conference, ServiceWave 2010, held in Ghent, Belgium, in December 2010. The 15 revised full papers presented were carefully reviewed and selected from 49 submissions. They cover a broad range of subjects related to service-oriented architectures and the underlying cloud infrastructure and are organized in topical sections on cloud computing, service adaptation and identification, infrastructures, applications and mashups, and engineering of service-oriented applications. In addition to the scientific track, 24 extended abstracts of demonstrations covering a wide spectrum of technology and application domains were accepted out of 31 submissions.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Computer Science; Computer Communication Networks; Software Engineering; Information Systems Applications (incl.Internet).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Programming Techniques